(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
Public health recommendations and government measures during the COVID-19 pandemic have resulted in numerous restrictions on daily life including social distancing, isolation and confinement at home. While these measures are necessary to limit the spread of COVID-19, the impact of these restrictions on healthy behaviors and lifestyles in the home is not specified. This research presents the results of the respondents about consumer behavior and consumption patterns of families in Sulaymaniyah governorate in aspects of nutrition, clothes and sanitary items the research follows the method of a questionnaire form along with the review of previous studies, and the research reached a group of theses One of the most important conclusions is that the Coronavirus pandemic has a direct impact on consumers’ behavior in terms of spending their incomes with the increase and decrease in their demand for certain types of goods and services As the research reached that those preventive and health materials from among the selected commodities, the demand for them has increased significantly since the emergence of the Corona pandemic. Finally, the research suggested a set of recommendations, some of which are related to consumers, which includes a review of their income expenditure and not to over-purchase medical materials and goods Some of the others are related to governments with regard to providing some necessary goods and services, including medical materials and goods, for free or at a lower price, and finding a quick solution to this bad situation that the economy of the Kurdistan region is going through.